Systematic Irrationality and the Emergence of Behavioral Economics - Till Neuhaus (Journal of Interdisciplinary History of Ideas, 2023)
Rational choice theory is one of the theoretical pillars on which the discipline of economics rests. Equipped with this theoretical basis, scholars attempted to explain a wide array of circumstances. However, from the 1960s onwards, different scholars from the field of psychology found evidence that deviations from rationality occur in systematic fashion. This not just created a new field of psychological research but also questioned rational choice theory. Ultimately, the two disciplines merged and formed what is nowadays known as behavioral economics. This article attempts to reconstruct the debates taking place at the economics-psychology nexus but focusing on the axioms of rational behavior as brought forward by von Neumann and Morgenstern (1944). In a second step, these developments will be discussed from a philosophy as well as sociology of science perspectives. Lastly, this article will try to isolate necessary pre-conditions for the hybridization of ideas as the emergence of behavioral economics can be considered the successful hybridization of economics and psychology.